What anthropologists do - Strang, Veronica, author.
1 online resource (1 volume)
Keywords: "Why should you study anthropology? How will it enable you to understand human behaviour? And what will you learn that will equip you to enter working life? This book explores the many career options available to those trained in anthropology, and describes what studying anthropology actually means in practice. Anthropology gets under the surface of social and cultural diversity to understand people's beliefs and values, and how these guide the different lifeways that these create. This accessible book presents a lively introduction to the ways in which anthropology's unique research methods and conceptual frameworks can be employed in a very wide range of fields, from environmental concerns to human rights, through business, social policy, museums and marketing. This new updated edition includes an additional chapter on anthropology and interdisciplinarity. This is an essential primer for undergraduates studying introductory courses to anthropology, and any reader who wants to know what anthropology is about"--